A Multi Media Approach to the Teaching of Oral Skills - Lee, Kim Seoh Julia (Journal of Modern Languages, 2017)
This paper considers the role of audio and video recordings in the UMSEP’s materials. Audio and video recordings are part and parcel of the UMSEP teaching materials are to be regarded as an enhancement and as lids to the teaching programme and not as independent programmes in themselves. Their use has been carefully integrated with the printed materials to make the learning/teaching process more effective and certainly more motivating for students.